Think like a feminist the philosophy behind the revolution - Hay, Carol 1977- (W.W. Norton & Company, 2020)
"An audacious and accessible guide to feminist philosophy-its origins, its key ideas, and its newest directions. Think Like a Feminist is an irreverent yet rigorous primer that unpacks two hundred years of feminist ideas. Professor Carol Hay takes the long view on our current moment, framing it within the philosophical thinking that underlies the organization and activism that has transformed women's roles and lives. She delves into topics such as the role of oppression, gender roles, sexual violence, what it means to identify as a woman, and the intersections of sexism, racism, classism, and homophobia. Hay shatters common misconceptions about feminism as she sheds light on the social structures that continue to restrict women. From the historical work of feminists such as Mary Wollstonecraft and Simone de Beauvoir to influential feminist theorists of today-including bell hooks, Judith Butler, Kimberlé Crenshaw, and María Lugones-Hay builds a toolkit that explains how and why sexism hurts women and offers practical strategies to continue the work of dismantling it. By conveying the philosophy underlying feminism, Think Like a Feminist brings today's feminism into focus, so we can deliberately shape the feminist future"--
Keywords: Feminismus; Geschlechterforschung; Feminist theory; Feminism